2017
DOI: 10.3390/s17092047
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Mode Electro-Optical Techniques for Biosensing Applications: A Review

Abstract: The monitoring of biomolecular interactions is a key requirement for the study of complex biological processes and the diagnosis of disease. Technologies that are capable of providing label-free, real-time insight into these interactions are of great value for the scientific and clinical communities. Greater understanding of biomolecular interactions alongside increased detection accuracy can be achieved using technology that can provide parallel information about multiple parameters of a single biomolecular p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 97 publications
0
26
0
Order By: Relevance
“…Electrochemical-surface plasmon resonance (EC-SPR) combines SPR sensing capability based on binding-induced refractive index changes at the electrode-electrolyte interface with electrochemical sensing capability on the same electrode (Hu et al 2008). This approach has been used for monitoring molecular binding events (Juan-Colas et al 2017) and could potentially be applied to selective detection of pathogens.…”
Section: Integration Of Complementary Transduction Elementsmentioning
confidence: 99%
“…Electrochemical-surface plasmon resonance (EC-SPR) combines SPR sensing capability based on binding-induced refractive index changes at the electrode-electrolyte interface with electrochemical sensing capability on the same electrode (Hu et al 2008). This approach has been used for monitoring molecular binding events (Juan-Colas et al 2017) and could potentially be applied to selective detection of pathogens.…”
Section: Integration Of Complementary Transduction Elementsmentioning
confidence: 99%
“…It is stated that OWLS is superior to QCM. Interesting is the combination of OWLS and electrochemistry to monitor the adsorbed mass of charged molecules and to study the reversibility of a adsorption processes [258].…”
Section: Waveguides With External Periodic Structurementioning
confidence: 99%
“…Possibilities for multi‐domain sensing, which may include simultaneous, e. g., optical, electrical or mechanical interrogation, has been intensively explored in the last decade . Study in additional domains may enhance information about the investigated sample or provide confirmation of results received in the other domain.…”
Section: Introductionmentioning
confidence: 99%
“…Thin ITO films have similarly been applied for combined optical and EC analysis on planar and optical fiber sensing devices, but in this case ITO was applied mainly in order to initialize EC‐induced polymerization of a compound necessary for further detection procedure . Meanwhile, it has been found that when the potential is applied to the electrode in opto‐EC setup and both optical and EC responses are investigated simultaneously, significantly more information can be received about the investigated medium than when the responses are studied separately .…”
Section: Introductionmentioning
confidence: 99%